The politics of economic adjustment : international constraints, distributive conflicts, and the state - Haggard, Stephan; Kaufman, Robert R. (Princeton University Press, 1992)
In the 1980s some developing countries adopted orthodox market-oriented policies in response to international economic crises, others experimented with alternative programs, and still others failed to develop coherent adjustment strategies of any sort. Building on the case studies in Economic Crisis and Policy Choice, these essays offer comparative analysis of these divergent experiences with macroeconomic stabilization and structural adjustment. Barbara Stallings and Miles Kahler explore the external pressures on governments. Peter Evans and John Waterbury examine the role of the state in the adjustment process, Evans through the lens of earlier historical experience with economic restructuring, Waterbury by focusing on the politics of privatization. Joan Nelson analyzes the politics of income distribution in the adjustment process, and Haggard and Kaufman investigate the political correlates of inflation and stabilization. A final essay assesses the prospects for combining market-oriented reforms with political democratization.
Keywords: Structural adjustment (Economic policy); Economic stabilization.; Ajustement structurel (Économie); Stabilisation économique.; BUSINESS & ECONOMICS -- Industries -- General.; Economic stabilization; Stabilitätspolitik; Entwicklungsländer; Wirtschaftslenkung; Buitenlandse schulden.; Economische politiek.; Internationale economische betrekkingen.; Estabilizacao economica.; Paises subdesenvolvidos (economia); Stabilisation économique -- Pays en voie de développement.; Ajustement structurel.; Aufsatzsammlung.; Kongreß -- New Haven (Conn.) -- 1985.